(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the foundational role of national and universal values in constructing the basis of a third renaissance in New Uzbekistan. It highlights the priority social issues related to fostering human virtues in youth, such as friendship, hospitality, humanitarianism, moral integrity, generosity, kindness, creativity, freedom, cheerfulness, optimism, courage, sincerity, courtesy, love for the homeland and its people, diligence, honesty, respect for the past, national pride, patriotism, and nationalism.